(untitled) (Archaeologia Adriatica, 2010)
Graves in settlement areas during the 9th-10th cent. represent a rare way of inhumation. Analysis of finds provided determining traits of all elements of burial rite. Only when further sources of historical character were added it was possible to determine the reasons for inhumation in settlements.The reasons lie with the exceptionality of the deceased. These persons could get into this position after having broken valid law they died and were not able to amend their failures. This second-rate social status of similar character could have been obtained also by other individuals who had died in uncommon way or under unclear conditions. This way of inhumation does not represent some phenomenon of a crisis, but it is evidence for growing legal consciousness of members of the Great Moravian society.